Cosmetic Tourism in Northern Ireland. Issue 6 (December 2019) - Martin, Serena; Long, Rebekah; Hill, Christopher; Sinclair, Stephen
Abstract : Aim: Over the new year period, we recognized a high number of admissions with postoperative complications following cosmetic surgery abroad. We aimed to determine the driving forces behind this and financial impact on the National Health Service (NHS). Methods: Cases of all patients attending the regional plastic surgery unit with complications following surgery abroad were reviewed. Patients completed a survey on the perioperative period abroad and driving forces. In addition, the costing department was contacted to determine the financial burden associated with cosmetic tourism. Results: Six patients were admitted to the regional unit after independently organizing surgery abroad. Countries visited included Turkey, Belgium, Poland, Estonia, and India. Reasons included cost and access to procedures not recommended by UK surgeon. Type of surgery included breast (5), abdominoplasty (2), liposuction (2), and labiaplasty (1), and 50% had multiple procedures. Complications included necrotic wounds (33%), infected breast implant (33%), venous thromboembolism investigated (33%), and wound infection (17%). Overall, 67% required surgery on the NHS. The total cost was £23, 976.82, with an average of £4000/patient (range, £1294–£6291). Discussion/Conclusions: This surge in cosmetic complications occurred in the New Year period. Complications were seen after a wide range of surgical procedures. All patients required an inpatient stay, and two-thirds required surgery with a significant cost burden to the NHS. Patients are unaware of the risks involved, highlighted by the lack of preoperative counseling and follow-up. In addition, this series has highlighted the risks associated with traveling in the perioperative period, with 2 patients investigated for pulmonary embolus.